Epidemiological study of COVID-19 effects on predisposing factors of adhesive capsulitis in patients referred to the physical medicine and rehabilitation clinic of Birjand University of Medical Sciences (Iran), During 2022-2023 - Shahab Tavakoli; Mryam Sadat Rahimi (مجله دانشگاه علوم پزشکی بیرجند)
Background and Aims: Adhesive capsulitis is a painful shoulder disease associated with fibrotic and inflammatory contracture of the rotator cuff, capsule, and ligaments. The present study aimed to investigate the epidemiological factors predisposing patients to frozen shoulders during the COVID-19 and post-COVID-19 eras. It also evaluated the role of COVID-19 infection or vaccination in adhesive capsulitis among patients referred to the Physical Medicine and Rehabilitation Clinic of Birjand University of Medical Sciences, Iran. Materials and Methods: In this descriptive study, the participants were 83 patients with adhesive capsulitis referred to the Physical Medicine and Rehabilitation Clinic of Imam Reza Hospital in Birjand City in Iran from September 23, 2022, to March 20, 2023. A checklist was completed according to the study's objectives, which included demographic information, such as age, gender, and anthropometric measurements of height and weight. Additionally, it recorded details about the dominant hand, affected hand, history of COVID-19 infection, history of vaccination against COVID-19 (including type and number of doses received), and any underlying diseases. Results: The mean age of the patients was 58.45±10.2 years. In addition, 59% of patients were female, 90.4% had the right dominant hand, and 59.1% of patients showed the occurrence of disease in the non-dominant shoulder. Moreover, 51.8% had a history of COVID-19 infection. All the examined patients had a history of the COVID-19 vaccination. Conclusion: In conclusion, old age, female gender, and diabetes were among the risk factors of adhesive capsulitis. According to this study and similar works from pre-COVID situations, with comparable risk factors and occurrences of frozen shoulder, it is likely that COVID-19 cannot be recognized as an independent risk factor. However, further studies in this field are recommended.